2011
DOI: 10.1111/j.1365-2133.2011.10438.x
|View full text |Cite
|
Sign up to set email alerts
|

The mesenchymal stem cell profile in psoriasis

Abstract: The microenvironment in psoriasis differs from those of atopic dermatitis and healthy skin; it could induce resident MSCs to produce angiogenic and proinflammatory mediators which lead to a reduction in the antioxidant capacity of these cells, contributing to the development of skin lesions in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 32 publications
3
73
0
Order By: Relevance
“…Mesenchymal stem cells were isolated from each skin specimen, maintaining the same features detected in our previous works [3,31].…”
Section: Isolation Culture and Characterization Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells were isolated from each skin specimen, maintaining the same features detected in our previous works [3,31].…”
Section: Isolation Culture and Characterization Of Mscsmentioning
confidence: 99%
“…The increasing focus on MSCs is due to the recent evidences on their possible involvement in different pathologies [32,36]. It has already been demonstrated that the altered microenvironment in psoriatic skin may induce the resident MSCs to produce angiogenic and pro-inflammatory mediators (VEGF, iNOS) leading to a reduction in the antioxidant ability of these cells, thus contributing to the pathophysiology of psoriasis [3,31]. In this view, we wonder if psoriasis could be considered a disease whose development starts early, in resident MSCs, which could show a typical phenotype, probably committed to develop psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriatic cutaneous lesions are promoted and sustained by T-cell and neutrophil infiltration into both dermis and epidermis, which leads to inflammation, causing a reduction of global antioxidant capacity of the skin. It has been suggested that increased reactive oxygen species (ROS) production and an aberrant antioxidant system may be the main factors in pathogenesis of psoriasis (6,17,38,57). ROS actively promote the secretion of inflammatory Th1 cytokines…”
mentioning
confidence: 99%
“…This discrepancy has been already described in a variety of models including also antimicrobial effector function [41] or in other cell types such as macrophages [42]. However, human skin-derived MSC seem able to produce NO especially when analysed in subject with psoriasis [43].…”
Section: Msc Immunosuppressive Properties In Vivomentioning
confidence: 91%